Long COVID syndrome, mortality and morbidity in patients hospitalized with COVID-19 from 16 countries: The World Heart Federation global COVID-19 study - Sliwa-Hähnle, Karen; Singh, Kavita; Nikhare, Kalyani; Kondal, Dimple; Raspail, Lana; Jain, Meetushi; Akter, Shahin; Talukder, Shamim Hayder; Kato, Toru; Bertagnolio, Silvia; Rylance, Jamie; Banerjee, Amitava; et al. (Global heart, 2025)
Background: Long-term adverse consequences of the COVID-19 infection affect many organ systems, which requires comprehensive understanding of the disease burden and determinants of persistent long COVID-19 symptoms in diverse population. However, data on long COVID complications are sparse, particularly from low- and middle-income countries (LMICs). The World Heart Federation (WHF) global study assessed the incidence of vascular complications, persistent long COVID symptoms and factors associated with mortality and major adverse cardiovascular events (MACE) among patients with COVID-19 up to one year after hospitalization. Methods: We recruited a total of 2535 patients hospitalized with COVID-19 and followed up to one-year post-hospital discharge. We collected data on long COVID symptoms, quality of life, and clinical outcomes, including new onset diseases, MACE, and mortality at 1-, 3-, 6-, and 9–12 months post-discharge. Descriptive and generalized estimating equation (GEE) regression analysis was performed to assess the factors associated with mortality and MACE. Findings: The majority of participants were recruited from LMICs (64%) and male (56%) with a mean (SD) age of 59.5 (20.0) years. Among those tested for COVID-19 strain (52%), Omicron strain was the most prevalent (98%). The follow-up rate at one year was 90%. Over half of the participants (56%) reported experiencing at least one major long COVID symptom (fatigue, breathlessness, anxiety, chest pain, and palpitations) at 1-month, and one-quarter participants reported persistent long COVID symptoms at 9–12 months. On the EQ-5D scale, 49% reported difficulties in usual activities, 33% reported anxiety/depression, and 23% reported problems in mobility within the first 6 months. The most frequent new-onset illnesses were pulmonary embolism (8%), kidney disease (4%), and hypertension (3%). The cumulative all-cause mortality rate was 15% (n = 382) at one-year post-discharge. Long COVID symptoms were more common among females, individuals with pre-existing comorbidities, and those with more severe acute illness. Age, obesity, ICU admission, and underlying cardiovascular or pulmonary disease were associated with increased risk of mortality and MACE. Conclusion: The study showed a substantial burden of mortality and morbidity, and a quarter of patients reported at least one persistent long COVID symptom after one year. Our findings underscore the need for early identification and management of long COVID symptoms in LMICs.